Combined use of vibrational spectroscopy and GC-MS methods in the characterization of archaeological pastes from Patagonia - Maier, Marta Silvia (2007)
Two samples of ochre painting residues (crayons) obtained from the archaeological site Cave Loncomán (Río Negro, Argentina) were analysed by ATR-IR and FT-Raman spectroscopy revealing the presence of haematite as the red pigment. Further analysis by FTIR of the chloroform/methanol extracts from both archaeological pastes showed the presence of carboxylic acids, indicative of hydrolysis of triacylglycerols in the pastes. Analysis by GC and GC/MS indicated that the main organic constituents of both pastes were saturated (C16:0 and C18:0) and unsaturated (C16:1 and C18:1) fatty acids. Our results show that the combined FTIR and Raman spectroscopic evaluation of archaeological pastes and their organic extracts provides a very useful and simple methodology to characterize the inorganic pigment and the presence of organic binders in an archaeological sample.